Dampak Pendampingan Orang Tua Dalam Pelaksanaan Pembelajaran Anak Di Sekolah (Deskriptif Kualitatif Di Paud Mekar Mandiri Kabupaten Seluma) - Rosidah, Rosidah; Margaretha, Lydia; Asnawati, Asnawati (Early Childhood Research and Practice, 2025)
The purpose of this study is to describe the impact of parental guidance in the implementation of children's learning at PAUD Mekar Mandiri School, Seluma Regency. The type of research used in this study is descriptive qualitative research. The data collection methods used are interviews, observations and documentation. The data sources are teachers and parents of PAUD Mekar Mandir children in Seluma Regency and documentation in the form of photographs during interviews with teachers and principals, namely data reduction, recording the results of interviews with teachers and parents, recording, coding data according to the information provided by informants, displaying data, describing the results of interviews with teachers and parents, and verifying data, rethinking the results of interviews, reviewing field notes, rethinking observation data and findings in the field, in order to draw conclusions from the results of the research that has been done. Based on the results of this study, it describes motivating children to learn, managing children's learning time and providing supporting facilities for children on the impact of parental guidance in the implementation of children's learning at PAUD Mekar Mandiri School, Seluma Regency. From the results of the study, it can be concluded that motivating children to learn by asking directly to the teacher or homeroom teacher, managing study time, giving children a break to play and then study and providing learning facilities by preparing a comfortable learning environment.